THE MARKET VALUE OF NON-FAMILY FIRMS: A STUDY ON OWNERSHIP CONCENTRATION, FINANCIAL POLICY, AND PROFITABILITY - Muchtar, Darmawati; Alias, Norazlan; Bensaadi, Iswadi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
This study investigates the market valuation effect of ownership concentration, financial policy, and profitability in a sample of 109 non-family from 2012 to 2019. We used balance panel data to investigate the market values and possible effects of the variables identified using the General Method of Moment (GMM) estimator. The market value is dynamic, which means that last year's market value significantly affects the current market value. Even though the majority shareholder is not a family member, the ownership concentration still has a significant negative effect on the market value. The financial decision shows that leverage has a positive and significant effect. At the same time, investment and dividend policy seems to have a negative effect on market value, although the investment is insignificant. Lastly, profitability has positive and significant effects on market value. This study contributes to non-family firm literature and provides new empirical findings and policy implications for regulators to enhance the market value. JEL: G11, G30, G32.